PELAKSANAAN UNDANG-UNDANG NOMOR 6 TAHUN 2011 TENTANG KEIMIGRASIAN MENGENAI TANGGUNG JAWAB PENJAMIN ATAS KEBERADAAN DAN KEGIATAN ORANG ASING DI BALI - Ngurah Mas Wijaya Kusuma (University of Udayana, 2014)
According to Article 1 (26) of the Laws Number 6/2011 concerning Immigration, the term guarantor is well known. The guarantor is a person or a corporation responsible for the existence and activities of foreigners while they are in Indonesia. The term guarantor, at the time when the Laws Number 9/1992 concerning Immigration come into force has been replaced with the term sponsor whose meaning is not far from the term guarantor. The purpose of a guarantor for certain foreigners is that there are parties who are responsible for them during their stay and activities in Indonesia and even the parties see to their going home when their stay permit ends or finance them in their process for going home if they are deported. The other purposes are to make their stays and activities beneficial and advantageous to the local community so that stability and public interests remain to be maintained. However, the reality field in Bali, many underwriters foreigners who are not responsible and do not obligations stipulated in law No.6 of 2011. Irresponsible guarantor can be seen from the caresless for the existence and activities of foreigners so often misuse a residence permit or concurrent positions without permission and is located in Indonesia exceeded the time limit given or overstayed. Guarantors obligations can not be seen from the number of foreigners who do not report any change of address to the immigration office. This study is an empirical legal research based on under law No 6 of 2011 on immigration is associated with the fact that the field deskriptif qualitative approach. The research condected in the area that includes counties delinquent bali, Denpasar city, district and county Gianyar and Buleleng. Data is sourced research on primary data and secondary data. The main source of this study is that the guarantor strangers individual and corporate guarantor. Secondary data obtained from the immigration officer. Primery data and secondary data sources supported by primary legal materials that Undang-undang No.6 in 2011 and legislation on immigration. Data collection techniques used are interview techniques and questionnaire techniques. Lack of responsibility of the quarantors of the existence and activities of foreigners, due to lack of knowledge will be the quarantor liable as quarantor in particular the activities of foreigners. Assume that the quarantor has a limited residence permit foreigners can work anywhere. Lack of responsibility of a quarantor is also caused by the still weak immigration law enforcement in investigating any criminal cases immigration. Quarantor responsibility for the existence and activities of foreigners in bali, yet runs effectiveness.